Aplicación de M.E (microorganismos eficientes) como probiótico, promotor de crecimiento en toretes de ceba en el barrio Muligua del cantón Pangua provincia de Cotopaxi - Alvear Soria, Marcelo Javier (2011)
His research was developed in the subtropics of the province of Cotopaxi, specifically in the Canton Pangua. This paper evaluates the three doses of efficient microorganisms (EM), used as probiotics and applied to three groups of fattening bulls. A fourth group of animals serves as a witness, it is exempt from the application of the product. In chapter one of this writing, the bibliographic information is collected regarding the characteristics of the micro flora of the stomach of ruminants, the use of probiotics in animal nutrition, the particularities of the EM. In chapter two are part of the methods, materials, and design of the experiment. Breeding during the study period, the development in housing and feeding of animals grazing in the area use. In Chapter three discusses the data obtained from measurements of feed intake and increased the size of the animals in order to establish statistically whether the use of this microbial culture can improve the development of animals....